Responses of melanocytes and melanomacrophages of Eupemphix nattereri (Anura: Leiuperidae) to Nle4, D-Phe7-α-melanocyte stimulating hormone and lipopolysaccharides - Franco-Belussi, Lilian [UNESP]; Castrucci, Ana Maria de Lauro; de Oliveira, Classius [UNESP] (Elsevier, 2013)
Melanocytes are found in various organs of ectothermic animals, playing a protective role against bacteria and free radicals. It is known that pigment cells from hematopoietic organs have immune functions. However, the role of visceral melanocytes is not well understood. Cutaneous melanocytes are responsive to α-melanocyte stimulating hormone (α-MSH), which is associated with the dispersion of melanin granules within melanocytes. α-MSH has also been reported to inhibit most forms of inflammatory responses by decreasing the pro-inflammatory cytokines and neutrophil migration. The present study evaluated the influence of an α-MSH analog (Nle4, D-Phe7-α-MSH) and lipopolysaccharides (LPS) from Escherichia coli on the liver and testicular tissues of the anuran Eupemphix nattereri. The tested hypotheses were: (i) the pigmented area will increase following hormone and LPS administration, (ii) pre-treatment with α-MSH will decrease the number of mast cells, and (iii) the hormone will have protective effects against LPS-induced responses. We found that hormone administration did not change hepatic pigmentation, but increased testicular pigmentation. Testicular pigmentation quickly increased after LPS administration, whereas there was a late response in the liver. The response of enhanced pigmentation was delayed and the number of mast cells decreased in animals previously treated with the α-MSH analog when compared to the LPS group. Hemosiderin and lipofuscin were found in melanomacrophages, but not in testicular melanocytes. Although both the liver and the testes of E. nattereri have pigmented cells, these are distinct in morphology, embryonic origin, and pigmentary substances. These differences may be responsible for the different responses of these cells to the α-MSH analog and LPS administration. © 2013 Elsevier GmbH.
Keywords: Hemosiderin; Lipofuscin; Mast cells; Melanin; Pigmentation; Animalia; Anura; Bacteria (microorganisms); Escherichia coli